Gut microbiota-dependent trimethylamine-N-oxide (TMAO) shows a U-shaped association with mortality but not with recurrent venous thromboembolism. Issue 174 (February 2019) - Reiner, Martin F.; Müller, Daniel; Gobbato, Sara; Stalder, Odile; Limacher, Andreas; Bonetti, Nicole R.; Pasterk, Lisa; Méan, Marie; Rodondi, Nicolas; Aujesky, Drahomir; Angelillo-Scherrer, Anne; Matter, Christian M.; et al.
Abstract: Introduction: Gut microbiota-dependent trimethylamine- N -oxide (TMAO) correlates with arterial thrombotic events including myocardial infarction and stroke, and mortality. However, the association of TMAO with recurrent venous thromboembolism (VTE) and mortality remains unknown. Methods: TMAO plasma levels were assessed by high performance liquid chromatography in 859 patients aged ≥65 years with acute VTE and categorized into low (<2.28 μmol/L), medium (2.28–6.57 μmol/L), and high levels (>6.57 μmol/L) based on the 25th and 75th percentile. Associations of TMAO with recurrent VTE, major or non-major bleeding, and mortality were investigated. Results: During a mean follow-up of 28 months, 106 patients developed recurrent VTE, 259 had major or non-major bleeding events, and 179 patients died. The risk of recurrent VTE did not differ significantly between patients with low, medium (adjusted subhazard ratio [SHR], 1.38; 95% confidence interval [CI], 0.81 to 2.36; p = 0.232) and high TMAO levels (SHR, 1.44; 95% CI, 0.80 to 2.58, p = 0.221). Compared with low TMAO levels, the adjusted hazard ratio [HR] for mortality was 0.68 (95% CI, 0.47 to 0.98, p = 0.039) in patients with medium TMAO levels and 1.02 (95% CI, 0.68 to 1.52, p = 0.922) in patients with high TMAO levels. Fractional polynomial Cox-regression confirmed a U-shaped association (adjusted p = 0.045), with the lowest mortality risk in patients with TMAO around 4 μmol/L. TMAO was not associated with major or non-major bleeding. Conclusion: TMAO showed a U-shaped association with mortality in elderly patients with acute VTE and was not associated with recurrent VTE and major or non-major bleeding. Highlights: Association of TMAO with recurrent VTE or mortality was investigated in 859 patients. TMAO showed a U-shaped association with mortality in elderly patients with acute VTE. TMAO was associated neither with recurrent VTE nor with major or non-major bleeding.